The Determinants of Tax Buoyancy: An Experience from the Developing Countries (The Pakistan Development Review, 1994)
International comparison of fiscal efforts of developing countries was a fascinating area of public finance in the 1960s and 1970s. The famous studies in this area were Harley (1965); Lotz and Morss (1967); Raja (1971); Raja et al. (1975) and Roy (1979). Most of these studies used ordinary least square (OLS) technique to estimate the determinants of the total tax to GDP ratio and the most common exogenous variables used by these studies were share of agriculture sector, share of industrial sector, share of foreign trade and per capita income. Some studies used the level of monetisation, somes used the. level of education and other used the level of urbanisation as exogenous variables in the estimation of tax potential of different developing countries. The present study instead of exploring the determinants of tax to GDP ratio attempts to explore the determinants of buoyancy of the taxes i.e. the total taxes, direct taxes and indirect taxes. The buoyancy of a tax measures the total response of tax revenue to change in income. The scope of the study also includes the ranking of developing countries on the basis of actual to predicted values of these buoyancies. The study would have been more useful if the study could fmd the determinants of the elasticity of these taxes, but due to nonavailability of data on the discretionary measures for each tax this was not feasible. The paper is organised as follows, Section I describes the theoretical basis of the model, Section II gives methodology and data collection, Section III gives results of the model and Section IV summarises the main conclusions.